2012
DOI: 10.1108/00251741211194921
|View full text |Cite
|
Sign up to set email alerts
|

Open innovation in the public sector of leading countries

Abstract: Purpose -The purpose of this study is to examine the current open innovation practices in the public sector of leading countries. Design/methodology/approach -Using a framework based on the role of the government in open innovation, this study analyses a profile of early open innovation adopters based on collected data from secondary sources. Findings -First, the USA, Australia and Singapore developed open innovation policies at the national level, facilitating a positive innovation climate. Many projects, esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
164
1
19

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(198 citation statements)
references
References 24 publications
5
164
1
19
Order By: Relevance
“…Studies have analyzed the differences in collaboration success factors driven by collaboration purpose (such as technology development or business expansion) and collaboration partner (such as the government and universities [16][17][18]). Möller and Rajala [60] suggested three types of business networks including current business nets, business renewal nets and emerging new business nets and then showed that they pose wide different conditions and requirement for collaboration.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Studies have analyzed the differences in collaboration success factors driven by collaboration purpose (such as technology development or business expansion) and collaboration partner (such as the government and universities [16][17][18]). Möller and Rajala [60] suggested three types of business networks including current business nets, business renewal nets and emerging new business nets and then showed that they pose wide different conditions and requirement for collaboration.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…This stems from the view that government organizations can realize services that are aligned with public values by interacting with the knowledge sources from outside [31]. In such interactions, the government's role is redefined as one that supports the citizens in active self-expression or in the fulfilment of common interests [32], whereas the citizens' role is redefined as the joint producer of policies [33]. Such a re-definition of roles is accompanied by massive changes in government organizations, the character of which may be summarized as breaking out from vertically integrated organization structures or citizen orientation [34].…”
Section: The Significance and Methods Of Utilizing Open Innovationmentioning
confidence: 99%
“…Although developed countries and numerous public organizations recognize that they must reflect citizens' opinions or expert knowledge in policies by opening up, they continue to show an unenthusiastic tendency towards organizational innovation [33]. This is due to the ambiguity surrounding the means of responding to the complexities of citizen issues and demands.…”
Section: The Advantages Of Using Design Thinking In Policy Processesmentioning
confidence: 99%
“…Empowerment compels employees to be motivated and enthusiastic in utilizing their distinctive capabilities and creativity towards organisational survival (Sharma and Kaur 2011). Employees' empowerment is also one of the strategies that organisations use to drive innovative thought that foster creative abilities (Lee et al 2012, Moses et al 2016. Employee empowerment to take initiatives, participate in decision making process, solving problems and taking charge of projects as well as having freedom to get the job done require clear effective communication and feedbacks (Elnaga and Imran 2014).…”
Section: Employees' Empowerment and Organisational Survivalmentioning
confidence: 99%